Current Mode Control of Non-Isolated Multi-Phase Interleaved Buck-Boost Converter for Military Battery Charging Application. - Ali Shaibu; Ahmet Karaarslan (Department of Electrical Engineering ITS and FORTEI, 2022)
Power conversion devices are essential in a remote off-grid site, typically for military purposes where several types of equipment with varying input characteristics are supplied essentially by the same energy source, necessitating the use of a buck-boost converter for DC-DC applications. Because the conventional buck-boost converter's inverting output voltage is incompatible with some applications, the two-switch buck-boost converter is recommended for battery charging in military applications. The nominal input voltage range of the five-phase interleaved buck-boost converter is 9 – 36 V, the output voltage is 28 V, the output power is 3.3 kW, and the switching frequency is 100 kHz. The simulation of the converter with current mode control in the MATLAB/Simulink simulation environment was performed to confirm validity of the operational theory and the simulation results show consistency with theoretical values. Maximum of 74.41 ms and 51.35 % were recorded under all conditions of operation for the settling and overshoot respectively. The obtained data indicates a 1–2 % variation between the measured and theoretical duty cycle.